2016
DOI: 10.1007/s10549-016-3687-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidental radiologic findings at breast cancer diagnosis and likelihood of disease recurrence

Abstract: Purpose Despite guidelines recommending against its routine use, perioperative imaging for distant metastases is frequently performed in newly diagnosed breast cancer patients, uncovering incidental findings of uncertain significance. We assessed the clinical significance of incidental findings by determining if their presence is associated with disease recurrence. Methods A retrospective review of staging imaging was performed in patients with stage II or III invasive breast cancer diagnosed 2008–2009 at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
3
20
1
1
Order By: Relevance
“…The likelihood of having metastatic disease in this setting has been demonstrated to be less than 2% in multiple studies. 14,15 Harm from performing unnecessary imaging can include the cost of testing to patients and society, radiation exposure from the imaging tests, and anxiety related to testing.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of having metastatic disease in this setting has been demonstrated to be less than 2% in multiple studies. 14,15 Harm from performing unnecessary imaging can include the cost of testing to patients and society, radiation exposure from the imaging tests, and anxiety related to testing.…”
Section: Discussionmentioning
confidence: 99%
“…50 These recommendations are based on studies showing no additional value of these tests in patients with early-stage disease. [51][52][53] In one study, metastases were identified by bone scan in 5.1%, 5.6%, and 14% of patients with stage I, II, and III disease, respectively, and no evidence of metastasis was detected by liver ultrasonography or chest radiography in patients with stage I or II disease. 51 For patients with stage III breast cancer, the prevalence of positive results on liver ultrasound and chest radiography was 6% and 7%, respectively.…”
Section: Additional Workupmentioning
confidence: 99%
“…However, only 12% were eventually diagnosed with DM. 13 Furthermore, this approach may lead to delays in the treatment delivery, have negative impact on the cost of care, and cause unnecessary psychological distress to patients. On the other hand, failure to properly diagnose DMs during the initial workup may also lead to an inappropriate treatment, such as unnecessary local surgery and/or radiation and adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%